Effects of viscosity modifying admixture (VMA) on workability and compressive strength of structural EPS concrete. (30th June 2018) - Li, Chao; Miao, Linchang; You, Quan; Hu, Shengkun; Fang, Huanglei
Highlights: A class of structural EPS concrete was prepared by incorporation of fly ash. Effects of VMA on workability and strength of structural EPS concrete were studied. An effective dosage of VMA was recommended to inhibit segregation and anisotropy. Abstract: The lightweight expanded polystyrene (EPS) concrete has the characteristics of vibration energy absorption and can be used to conduct the metro track of vibration reduction and isolation. But the workability and compressive strength of the lightweight EPS concrete need to be improved in the engineering application of vibration energy absorption when EPS beads are mixed in concrete. To improve the workability and compressive strength, this paper investigated the effects of viscosity modifying admixture (VMA) on the workability, segregation resistance, compressive strength and failure mode of a class of structural lightweight EPS concrete, prepared by controlling a certain water-binder ratio and fly ash replacement. The dosage of VMA in the mixtures was 0.02%, 0.04%, 0.06%, 0.08% and 0.10% by weight of the total cementitious materials (TCM), respectively. Workability was investigated through a multi-index of slump, slump flow, T50 and inverted slump cone time while segregation resistance was evaluated by a density test. The concept of anisotropy was employed to evaluate the compressive strength and failure mode. Results showed that VMA had significant negative effects on the fluidity of structural EPS concrete. From the density test results, VMA significantly enhanced the resistance to segregation and the segregation degree of EPS concrete exhibited a negative linear correlation with the dosage of VMA according to the definition of segregation index (SI). The compressive strength decreased substantially with increase of VMA and the anisotropy of the strength was shown to be inhibited gradually with increase of VMA, resulting from the improvement of resistance to segregation. As the elimination of anisotropy, the failure modes were altered consequently. In terms of the effectiveness to inhibit the segregation and the anisotropy, 0.10% by weight of TCM was recommended as the most effective dosage for VMA in this paper.